Novel targeted inhibition of the IL-5 axis for drug reaction with eosinophilia and systemic symptoms syndrome - Rubin, Limor; Talmon, Aviv; Ribak, Yaarit; Kessler, Asa; Martin, Yossi; Haran, Tal Keidar; Shamriz, Oded; Adini, Irit; Tal, Yuval (Frontiers in Immunology, 2023)
Background: Drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome represents a severe hypersensitivity reaction. Up-to-date treatment is based on withdrawal of medication, supportive care, and immunosuppression using high-dose corticosteroid (CS) therapy. However, evidence-based data are lacking regarding second-line therapy for steroid- resistant or steroid-dependent patients. Objectives: We hypothesize that the interleukin (IL)-5 axis plays a critical role in the pathophysiology of DRESS, and hence inhibition of this signaling pathway could offer a potential therapy for steroid-depended and/or steroid-resistant cases and it may offer an alternative to CS therapy in certain patients more prone to CS toxicity. Methods: Herein, we collected worldwide data on DRESS cases treated with biological agents targeting the IL-5 axis. We reviewed all cases indexed in PubMed up to Oct. 2022 and performed a total analysis including our center experience with two additional novel cases. Results: A review of the literature yielded 14 patients with DRESS who were treated with biological agents targeting the IL-5 axis, as well as our two new cases. Reported patients are characterized by a female to male ratio of 1:1 and a mean age of 51.8 (17-87) years. The DRESS-inducing drugs, as expected from the prospective RegiSCAR study were mostly antibiotics (7/16): vancomycin, trimethoprim-sulfamethoxazole, ciprofloxacin, piperacillin-tazobactam and cefepime. DRESS patients were treated with anti-IL-5 agents (mepolizumab and reslisumab) or anti-IL-5R biologics (benralizumab). All patients have clinically improved under anti-IL-5/IL-5R biologics. Multiple doses to achieve clinical resolution were needed in mepolizumab whereas single dose of benralizumab was often sufficient. Relapse was noted in one patient receiving benralizumab treatment. One patient receiving benralizumab had a fatal outcome, although mortality was probably related to massive bleeding and cardiac arrest due to COVID-19 infection. Conclusions: Current treatment guidelines for DRESS are based on case reports and expert opinion. Understanding eosinophil central role in DRESS pathogenicity emphasize the need for future implementation of IL-5 axis blockade as steroid-sparing agents, potential therapy to steroid-resistant cases, and perhaps an alternative to CS treatment in certain DRESS patients more prone to CS toxicity.